Replacement Value of Low Tannin Sorghum (Sorghum bicolor) for Maize in Broiler Chickens’ Diets in the Semi-Arid Zone of Nigeria - I.D, Kwari,; Diarra , S.S.; Igwebuike, J.U.; Nkama, I.; Issa, S.; Hamaker, B.R.; Hancock, J.D.; Jauro, M.; Seriki, O.A.; Murphy, I. (International Journal of Poultry Science, 2012)
The decrease in the production coupled with the numerous industrial uses make maize an expensive energy ingredient for poultry feeding, thus the need for research into cheaper alternatives. A 9-week experiment was conducted to assess the effects of feeding low tannin sorghum grain as a replacement for maize on the growth, haematology and carcass measurements of broiler chickens at the Poultry Unit of University of Maiduguri Livestock Research Farm, Maiduguri, Nigeria. A total of 300 day-old broiler chicks were randomly allotted to 5 dietary treatments containing 3 replications of 20 chicks each. The diets contained sorghum grains at 0.00, 25.00, 50.00, 75.00, and 100% respectively as a replacement for maize. The starter and finisher diets were formulated to contain 23% and 20% crude protein respectively. The results of growth performance showed no superiority of maize over sorghum grain in terms of weight gain and feed conversion ratio, during both phases of growth (starter and finisher). Feeding sorghum grain had no adverse effect on the haematological parameters analyzed. The yields of carcass and cut-up parts were not adversely affected by the level of sorghum grain in the diet. Similarly, there was no adverse effect of feeding sorghum grain on the weight of vital organs (heart, liver and spleen). It was concluded that low tannin sorghum can completely replace maize in broiler chickens diets without compromising the growth, meat yield or the health of the birds. The substitution is beneficial as it reduces competition between poultry and man for the already scarce maize grain.